2019
DOI: 10.3389/fnins.2018.01029
|View full text |Cite
|
Sign up to set email alerts
|

Autism Pathogenesis: The Superior Colliculus

Abstract: After been exposed to the visual input, in the first year of life, the brain experiences subtle but massive changes apparently crucial for communicative/emotional and social human development. Its lack could be the explanation of the very high prevalence of autism in children with total congenital blindness. The present theory postulates that the superior colliculus is the key structure for such changes for several reasons: it dominates visual behavior during the first months of life; it is ready at birth for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 249 publications
(358 reference statements)
0
25
0
Order By: Relevance
“…The more primal and fast to react dorsal visual stream is highly operational during the first months of life, relaying low-resolution data from the rods with increased sensitivity to changes in the exterior scenery ( Hammarrenger et al, 2003 ; Bridge et al, 2016 ). The role of the superior colliculus (SC) in the dorsal stream has been recently highlighted, suggesting that in the neonatal period, this midbrain structure is pertinent for exercising focal oculomotor operations, receiving and integrating multimodal sensory inputs, and communicating with higher-order visual-neural configurations ( Pitti et al, 2013 ; Jure, 2019 ). The SC is, thus, highly involved in rudimentary social behaviors, including the preference to fixate on human faces and the ability to detect and imitate emotion-resonating facial expressions ( Jure, 2019 ).…”
Section: The Stem Of the Sensesmentioning
confidence: 99%
“…The more primal and fast to react dorsal visual stream is highly operational during the first months of life, relaying low-resolution data from the rods with increased sensitivity to changes in the exterior scenery ( Hammarrenger et al, 2003 ; Bridge et al, 2016 ). The role of the superior colliculus (SC) in the dorsal stream has been recently highlighted, suggesting that in the neonatal period, this midbrain structure is pertinent for exercising focal oculomotor operations, receiving and integrating multimodal sensory inputs, and communicating with higher-order visual-neural configurations ( Pitti et al, 2013 ; Jure, 2019 ). The SC is, thus, highly involved in rudimentary social behaviors, including the preference to fixate on human faces and the ability to detect and imitate emotion-resonating facial expressions ( Jure, 2019 ).…”
Section: The Stem Of the Sensesmentioning
confidence: 99%
“…The optic tectum, like its mammalian counterpart, the superior colliculus (SC), is a sensory processing hub that receives multimodal stimuli and is responsible for eliciting appropriate behavioral response 1 . Recently, the SC has received attention for a proposed role in autism spectrum disorder (ASD) pathogenesis due the essential role it plays in sensory perception 45 .…”
Section: Tectal Cell Populations Show An Upregulation Of Genes Implicated In Neurodevelopmental Disordersmentioning
confidence: 99%
“…A potential link between the SC and autism spectrum disorder (ASD) has been proposed as congenitally blind children are diagnosed with ASD at a higher rate than those born with no vision impairments 45,52 . As sensory processing impairments typically present in ASD, a structure such as the SC that receives and interprets sensory stimuli poses an interesting avenue for ASD investigations.…”
Section: The Optic Tectum May Provide a Useful Model For Autism Pathogenesis Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SC is an evolutionary ancient structure organized in functionally and anatomically distinct layers. While the upper layers are exclusively visual, the medial and deeper layers have multisensory and motor functions (27) . It has been suggested that this structure, via different output projections, mediates both orienting and avoidance responses to novel sensory stimuli (15, 17) .…”
Section: Discussionmentioning
confidence: 99%